Preferensi Konsumen Pengolah Terhadap Daging Ayam Lokal (Survei di Gerai Makanan Kawasan Bandung Raya) - Nuralfiyani, Amelia; Kuswaryan, Sondi; Herlina, Linda (Universitas Galuh, 2024)
Demand for local chicken meat continues to increase in line with population growth and changes in people's consumption patterns. This research was conducted to determine consumer preferences based on the attributes attached to local chicken meat and consumer attitudes towards local chicken meat. The research location was carried out at a food outlet that sells processed local chicken meat in the Greater Bandung area. Primary data was obtained from interviews with 35 local chicken meat sellers (as respondents). The analysis method used is the Chocran Q Test to determine what attributes are considered valid, Chi Square Analysis to determine preferences and Fishben Multiattribute Analysis to determine consumer attitudes towards local chicken meat. The results of the research show that the valid attributes are meat color, tenderness, freshness, cleanliness, aroma, chicken weight, price and location of purchase. The local chicken meat that consumers like and choose is meat that is pale white, slightly yellowish in color, has a distinctive chicken aroma, is free from shoot feathers, has a slightly tough texture and is medium in size with a price in the range of IDR 50,000 - IDR 65,000/kilogram purchased from local chicken farmer. An assessment of consumer attitudes towards purchasing local chicken meat shows that consumers have a